Immunocompetence of Two Broiler Strains Fed Marginal and High Protein Diets - Deif, E.A.; Galal, A.; Fathi, M.M.; El-Dein, A. Zein (International Journal of Poultry Science, 2007)
Immunocompetence of broiler chicks fed marginal and high dietary protein levels was studied. Four hundred one-day-old broiler chicks (200 Cobb and 200 Hubbard) were divided into two equal groups within each strain. The marginal protein starter diet had 3075 Kcal ME/kg and 20% Crude Protein (CP) while the marginal protein fishier diet had 3152 Kcal ME/kg and 18% CP. The high protein starter diet and finisher diets contained 3086 Kcal ME/kg, 22% CP and 3130 Kcal ME/kg, 20% CP, respectively. Starter ration was provided for ad libitum consumption from hatching up to 3 weeks of age, while the finisher one was provided from 4 to 6 weeks of age. The average high and low ambient temperatures recorded during the experimental period were 21 and 18°C, respectively. At 3 weeks of age, 60 chicks (15 chicks/strain/treatment) were used for determined the cell-mediated immunity via Phytohemagglutinin-P (PHA-P) injection. Also, humoral immune responses were determined. On day 14, chicks were slaughtered and the bursa of Fabricius, spleen, thymus, liver and heart were removed and weighed to the nearest milligram. The present results showed that the body weights did not significantly affected by strain, dietary protein level and their interaction. However, the Hubbard broiler chicks significantly consumed more feed and had a better feed conversion ratio compared to Cobb ones. The broiler chicks fed a high protein diet significantly consumed less feed and had a better feed conversion ration compared to other that fed a marginal protein diet. With respect to immunocompetence, it could be noticed that the Hubbard broiler chicks had significantly hyper responder to PHA-P injection and significantly higher total anti-SRBCs antibody titer compared to Cobb ones. The high dietary protein level significantly increased the toe-web swelling and total anti-SRBCs antibody titer compared to marginal protein level. The relative lymphoid organs weight did not significantly affected by strain. Similar trend, except for bursa, was noticed for dietary protein level. The relationships between body weight and toe-web swelling measured at all times were very low in Cobb fed a marginal protein diet. Similar trend, but moderate, was noticed in Hubbard-H group. However, significantly positive relationships between body weight and toe-web swelling measured at all times were observed in Cobb fed a high protein diet and Hubbard fed a marginal protein diet. Negative relationship between body weight and total anti-SRBC antibody titer was observed in all groups. In conclusion, under winter season of Egypt, the Hubbard broiler chicks had lower mortality rate and better immune competence compared to Cobb ones. Also, the high protein level improved the immunity of the broiler chicks.